Characterisation of paraffinic compositions in crude oils - Al-Kayiem, H.H. (Inderscience Enterprises Ltd., 2017)
The deposition and gelation of paraffin wax are among the significant risks in flow assurance during crude oil transportation. These risks are highly influenced by the structure of hydrocarbons in the produced composition from the well. In the present paper, four crude oil samples acquired from different Malaysian fields were experimentally analysed through gas chromatography/mass spectrometry, differential scanning calorimetry, and thermal gravimetric analyses. The crudes were investigated, with focus on the carbon number distribution, wax appearance temperature, and wax content. The results demonstrate that the crude oil samples with high molecular percentage of carbon distribution within a range of C20 to C40 comprehend high wax content. Measurement results of the four investigated crude samples revealed that the wax content is relatively high compared to other crudes produced in East Asian fields. Also, the four samples possess low wax appearance temperature characteristics, and all four crudes might behave as non-Newtonian at temperature around 38°C. The results provide useful information to manage the risk of wax formation in the transportation pipeline and the flow assurance of the crude. Copyright © 2017 Inderscience Enterprises Ltd.